Population characteristics of areolate grouper Epinephelus areo-latus (Forsskål 1775) from Terengganu waters, Malaysia - Nor Hazila Abdul Kadir (2020)
Growth parameters of areolate grouper, Epinephelus areolatus (Forsskål 1775) in Terengganu waters were determined by using length frequency analysis. A total of 606 samples from two main fish landing ports in Terengganu were collected monthly between February 2014 and January 2015. Growth parameters were estimated by using FISAT II (FAO-ICLARM stock assessment tools) computer software package, which includes a direct fit of length frequency data by ELEFAN I method. The von Bertalanffy growth parameters for E. areolatus from Pulau Kambing fish landing port were L∞ = 50.40 cm and K = 0.36 y-1 meanwhile samples from Kuala Dungun were L∞ = 48.30 cm and K = 0.32 y-1. The length weight relationship for E. areolatus from Pulau Kambing was y = 2.9546x – 4.1931, and from Kuala Dungun fish landing port was y = 2.9438x – 4.1492. The present research findings are important for future studies and relevant for the stock assessment and fishery management of E. areolatus in Terengganu waters.